UNDERSTANDING SHARENTING PRACTICES AMONG POSTGRADUATE MOTHERS - Yorika Indah Pratiwi Nababan; Indira Irawati; Rahmi Rahmi (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2026)
The phenomenon of sharenting, the practice of parents sharing information about their children on social media, has become increasingly prominent in global discourses on child privacy, digital ethics, and online parenting. While previous studies have extensively addressed the risks of sharenting, there is limited research explaining how educated mothers transform knowledge about privacy, ethics, and digital parenting into everyday sharing practices, particularly in non-Western contexts. This study aims to understand how graduate students who are also mothers internalize knowledge about sharenting and translate it into concrete practices on social media. The study used a descriptive qualitative approach with in-depth interviews, observation of Instagram posts, and documentation of six purposively selected informants. The results show that sharenting decisions tend to be reflective and negotiated through considerations of benefits, risks, emotions, social norms, and cultural and religious values. Informants displayed implicit forms of privacy literacy through strategies such as obscuring children's identities, limiting audiences, setting accounts to private, and delaying posts. These findings also demonstrate that subjective norms in sharenting practices are shaped not only by family and friends, but also by local values such as the concepts of ‘ain and pamali. Theoretically, this study extends the Theory of Planned Behavior in the context of non-Western digital parenting and demonstrates that the transformation of knowledge within the Knowledge-to-Action framework is not always linear. Practically, these findings emphasize the importance of privacy literacy and digital ethics that are sensitive to cultural context. However, because this study only involved six informants from a single institution, the findings are contextual and not intended to be broadly generalized.